Effects of seed size on soybean performance: germination, growth, stress resistance, photosynthesis, and yield - Xiyue Wang; Jixuan Sun; Zirui Yi; Shoukun Dong (BMC Plant Biology)
Abstract Background Seed size is an important quality trait in crops and is one of the key factors affecting crop yield; however, how seed size affects growth and physiological differences, stress resistance, and yield characteristics is unclear. Methods In this study, the effects of different seed sizes on germination, morphology, physiological characteristics, and yield traits of soybean were studied by combining germination, pot, and field experiments using Kenfeng 16 and Heinong 84 varieties. Results The germination potential, rate, and index, as well as the vigor index of very small seeds, were significantly lower than those of other seed sizes. Plant height and leaf area followed the order: large > medium > small > very small seeds. Dry matter accumulation in each organ was significantly higher in large seeds than in small seeds. Superoxide dismutase and peroxidase activity, soluble sugar, soluble protein, and proline content were highest in large seeds, whereas malondialdehyde content was highest in very small seeds. The SPAD value (an indicator of chlorophyll content) was highest in large seeds, whereas steady-state fluorescence yield and non-photochemical quenching were higher in large and medium seeds. In terms of yield characteristics, the performance of pot experiment was basically consistent with that of field experiment. The number of pods and seeds per plant was in the order of large > medium > small > very small seeds, and no significant differences were observed in plant height, bottom pod height, node number, or internode length. The 100-seed weight and yield of the large seeds were higher than those of the small or very small seeds. Conclusions Seeds of different grain sizes have differences in germination, which may be caused by differences in seed vigor. Medium to large seeds showed better growth effects in the field, including morphological parameters, photosynthetic parameters, etc. In addition, medium to large seeds also have better resistance levels and can better adapt to the environment. These factors ultimately lead to higher yields. This study promotes the further development of the production potential of excellent varieties, and provides valuable insights for soybean seed breeding and high-yield cultivation strategies.